Electronic Structure and Optical Properties of GaAs Doped with Rare-Earth Elements (Sc, Y, La, Ce, and Pr) - Yongrong Deng; Chunhong Zhang; Xinmao Qin; Wanjun Yan (Crystals)
Herein, the electronic structure and optical properties of GaAs doped with rare-earth elements (Sc, Y, La, Ce, and Pr) were evaluated using the first-principles method. Results showed that the lattice constants and cell volume of GaAs increased after doping. Band structure calculations indicated that the lowest conduction band and highest valence band were evident at the G-point, demonstrating that rare-earth-element doping did not alter the material type of GaAs, which remained a direct-bandgap semiconductor. The bandgap of Sc-doped GaAs increased, whereas those of Y-, La-, Ce-, and Pr-doped GaAs decreased. Moreover, the density of energy levels increased. Doping with Ce and Pr introduced impurity levels, and the Fermi level shifted into the conduction band. Investigation of the optical properties revealed that the static dielectric constant increased with La doping but decreased with Y, La, Ce, and Pr doping. The variation trends of the extinction coefficients of the doped samples were consistent with that of undoped GaAs: the extinction coefficient shifted to a low-energy region. In addition, a slight redshift occurred in the absorption spectrum. The absorption peak also diminished owing to rare-earth-element doping. We concluded that Ce- and Pr-doped GaAs can form metal alloys with different compositions. Such doping may provide a new class of materials for use in optoelectronic devices.